FORMING STUDENT CHARACTER THROUGH CIVIC EDUCATION LEARNING MODEL BASED PORTFOLIO IN SMP AL-WATHAN AMBON - Cecep Darmawan, Harmin Samiun, Dasim Budimansyah (Department of Civic Education, 2014)
The aim of this research was to describe about the former student character through Civic Education Learning Model based Portfolio. This research was used a Classroom Action Research. Throughout a purposive approach, this research was designed in a qualitative research. The result of research was indicate that student supporting and teacher better portfolioÂ model. An piquancy from the model namely the student can present positive character in the form of independence character, responsibility, caring to humanity, each other mengahargai one with other; dissimilar. Pursuant to above result, concluded by that teacher very support positive for learning by portofolio. For a while sided by a student, very enthusiastic and spirit of in applying the model.